2007
DOI: 10.1159/000111084
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dense Primary Chemotherapy, as Part of Multidisciplinary Treatment, for Inoperable Stage III B Breast Cancer – Long-Term Results of a Phase II Trial

Abstract: Background: Primary chemotherapy as part of multidisciplinary approach is the established treatment for inoperable stage III B breast cancer. The primary endpoints were conversion to operable disease and feasibility of conservative surgery (breast-conserving therapy: BCT); secondary were clinical and pathological complete response rate, local and distant control and safety of the primary regimen. Methods: Between 1998 and 2001, 40 inoperable breast cancer patients ≤60 years, 72% T4abc and 28% T4d, received 6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…In other randomized phase III trial [34] of preoperative infusional 5-fluorouracil, epirubicin, and cisplatin (infusional ECisF) versus conventional doxorubicin and cyclophosphamide (AC) (TOPIC1), the pCR in breast including DCIS were similar (24 and 25%, respectively); at median follow-up of 5 years, the OS was 82% for ECisF and 74% for AC (P = 0.18). Recently, Massidda et al [35] reported of pCR using Sataloff's classification of 32% in both breast and axilla using dose dense of cisplatin, epirubicin, and vinorelbine (PEV) regimen every 2 weeks with G-CSF support in T4 and inflammatory breast cancer; at median follow-up of 7 years the reported DFS and OS was 75 and 80%, respectively, which is similar to our result. Among our relapsed patients, 46% was Her2 positive.…”
Section: Discussionsupporting
confidence: 89%
“…In other randomized phase III trial [34] of preoperative infusional 5-fluorouracil, epirubicin, and cisplatin (infusional ECisF) versus conventional doxorubicin and cyclophosphamide (AC) (TOPIC1), the pCR in breast including DCIS were similar (24 and 25%, respectively); at median follow-up of 5 years, the OS was 82% for ECisF and 74% for AC (P = 0.18). Recently, Massidda et al [35] reported of pCR using Sataloff's classification of 32% in both breast and axilla using dose dense of cisplatin, epirubicin, and vinorelbine (PEV) regimen every 2 weeks with G-CSF support in T4 and inflammatory breast cancer; at median follow-up of 7 years the reported DFS and OS was 75 and 80%, respectively, which is similar to our result. Among our relapsed patients, 46% was Her2 positive.…”
Section: Discussionsupporting
confidence: 89%
“…Between 1990 and 1996, the patients received older standard primary chemotherapy regimens (eg, 5‐fluorouracil, epirubicin, and cyclophosphamide; epirubicin and cyclophosphamide; or cyclophosphamide, methotrexate, and 5‐fluorouracil). From 1996 onward, patients received new standard regimens, including intensified cisplatin‐epirubicin with or without taxanes 23…”
Section: Methodsmentioning
confidence: 99%